2018
DOI: 10.3889/oamjms.2018.366
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Ondansetron, Haloperidol, and Dexmedetomidine Efficacy for Prevention of Postoperative Nausea and Vomiting In Patients with Abdominal Hysterectomy

Abstract: AIM:This study was aimed to compare the effects of ondansetron, haloperidol, and dexmedetomidine for reducing postoperative nausea and vomiting (PONV) after laparoscopic cholecystectomy.METHODS:This randomised clinical trial study was performed on p.patients who were candidates for abdominal hysterectomy referring to Taleghani hospital in Arak. In this study, 114 patients with abdominal hysterectomy were randomly assigned to three groups (ondansetron, haloperidol, and dexmedetomidine) using the cubull randomis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Kamali A et al, in the study concluded that Ondansetron, when given prophylactically resulted in a significantly lower incidence of PONV than Haloperidol and dexmedetomidine. 8 Similar findings were found in a recent study conducted by University of Miami-Jackson Memorial Hospital, USA in which he noted that prophylaxis using Ondansetron and palonsetron have comparable in efficacy when used in prophyxais against PONV. 9 Role of Dexamethasone to decrease postoperative nausea and vomiting was assessed by Seki H. This was a study on how does dexamethasone influence surgical outcome after correction of idiopathic scoliosis.…”
Section: Ponv In the Study Groupsupporting
confidence: 83%
See 1 more Smart Citation
“…Kamali A et al, in the study concluded that Ondansetron, when given prophylactically resulted in a significantly lower incidence of PONV than Haloperidol and dexmedetomidine. 8 Similar findings were found in a recent study conducted by University of Miami-Jackson Memorial Hospital, USA in which he noted that prophylaxis using Ondansetron and palonsetron have comparable in efficacy when used in prophyxais against PONV. 9 Role of Dexamethasone to decrease postoperative nausea and vomiting was assessed by Seki H. This was a study on how does dexamethasone influence surgical outcome after correction of idiopathic scoliosis.…”
Section: Ponv In the Study Groupsupporting
confidence: 83%
“…Between the available drugs with this class; ondansetron is typically the most traditionally used for PONV prophylaxis. 8 Other scientific studies have displayed that dexamethasone reduces PONV after laparoscopic cholecystectomy. 11 The pooled meta-analysis of 7 RCTs advised that there were zero important dissimilarities between dexamethasone and ondansetron in the particular matter of the occurrence of PONV or postoperative anti-emetics used during the particular first 24 h right after laparoscopic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In orthopedic surgery, one of the main factors in limiting ambulation is pain, which can lead to thromboembolism as a result of immobility. 1 , 2 Therefore, pain management in such situations with the use of appropriate analytical techniques can be very important. One of the most effective and commonly used methods for postoperative pain management is the intravenous patient-controlled analgesia (IV PCA) after an orthopedic surgery.…”
Section: Ethical Publication Statementmentioning
confidence: 99%
“…7 However, its preemptive role in the prevention of PONV is under estimated where only few studies evaluated the incidence of PONV after prophylactic ondansetron administration before surgery. [8][9][10] We conducted this trial to evaluate the role of preemptive ondansetron in reducing the incidence of post-operative nausea and vomiting in liver donors.…”
Section: Introductionmentioning
confidence: 99%